Therapeutic Management of Right Side Congestive Heart Failure in a Dachshund Bitch - Talukdar, D. J.; Sarma, K.; Bayan, H.; Ahmed, F. A.; Das, G.; Behera, S. K.; Khiangte, L.; Dawngliana, MS (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Congestive Heart Failure (CHF) is a term that refers to the heart's inability to pump adequate blood  to the body. There are many causes of CHF in dogs viz. mitral valve insufficiency (MVI) or a leaky  mitral valve, dilated cardiomyopathy (Haggstrom, 2010) and chronic heartworm disease. Clinical  signs vary depending on whether the dog has left- or right-sided heart failure. Right-sided  congestive heart failure (RS-CHF) causes poor venous return to the heart, accumulation of fluid  in the peritoneum leading to ascites. Fluid also leaks from the veins in the limbs, causing oedema  of the peripheral region.